2004
DOI: 10.1111/j.1752-7325.2004.tb02722.x
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in Orthodontic Utilization and Treatment Need Among High School Students

Abstract: Minority groups and infrequent dental attenders may experience disparities in unmet orthodontic treatment need.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 12 publications
3
30
0
7
Order By: Relevance
“…Similarly, present study showed higher results of half and full cusp deviation compared to Onyeaso CO (2004). 16 While comparing according to DAI scores, the results of the current study are in correlation with Nelson S et al (2004). 17 A higher mean DAI score was noticed among males than females.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Similarly, present study showed higher results of half and full cusp deviation compared to Onyeaso CO (2004). 16 While comparing according to DAI scores, the results of the current study are in correlation with Nelson S et al (2004). 17 A higher mean DAI score was noticed among males than females.…”
Section: Discussionmentioning
confidence: 60%
“…16 While comparing according to DAI scores, the results of the current study are in correlation with Nelson S et al (2004). 17 A higher mean DAI score was noticed among males than females. The higher prevalence of malocclusion among males may be attributed to the differences in the adverse habits such as mouth breathing, nail biting, tongue thrusting and thumb sucking, etc.…”
Section: Discussionmentioning
confidence: 60%
“…2 Patients may not be considered suitable for orthodontic care by either the general practitioner or the specialist provider if they are irregular attenders or if their oral health and hygiene is poor. 6,9 Furthermore, research indicates that children from lower socio-economic groups are more likely to have discontinued orthodontic treatment than children from less deprived communities. 12 Social and cultural factors may impact upon the willingness of children to undertake a course of orthodontic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Whist sociodemographic characteristics do not appear to infl uence a child's perception of need for orthodontic treatment or aesthetic appearance, research indicates that boys and children from minority ethnic groups are less likely to receive care. [3][4][5][6] The infl uence of social deprivation on the uptake of services is less clear. Some studies have linked social deprivation and access to treatment with children from lower socio-economic groups being less likely to receive care, 3,[6][7][8] whereas other research has found no relationship between relative deprivation and the uptake of orthodontic services.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation